The Antecedent Interest in Micro-entreprises Toward Syariah Bank Financing in Yogyakarta - Wahyudin Wahyudin; Aftoni Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The development of Micro Small Businesses in Yogyakarta is very rapid and able to help the economy of the Yogyakarta region, but still has some problems, namely the problem of capital, this is what makes Islamic banks play a role in overcoming the problem. This study aims to determine the empirical evidence of the influence of profit-sharing factors, personal factors, and service to the interests of small micro-enterprises to finance the Yogyakarta Islamic Bank. This study uses a survey method using a research questionnaire distributed to entrepreneurs who enter the Micro Small Business category in the City of Yogyakarta. The source of data in this study is primary data and then the data is processed using SPSS software. Of the 70 questionnaires distributed only 60 questionnaires received answers from respondents. Data analysis techniques using data quality test, classic assumption test, and hypothesis testing (Multiple Regression Analysis, Determination Coefficient, F Test, and T Test).The results showed that the factors of profit sharing, personal factors, and service factors influenced the interest of Micro Small Enterprises to finance the Islamic Bank of Yogyakarta City. Keywords: profit sharing, personal factors, service, interest in financing